On some Salpingoporella species from the Lower Cretaceous of Dinaric karst - Sokač, Branko (Array, 2008)
Summary: In this paper a new species Salpingoporella tari n.sp. is established, found in a sample of Barremian intraclastic grainstone. It is similar to S. annulata (LORENZ) and S. grudii (RADOIČIĆ), but visibly more robust. It has few branches per whorl, and the whorls being spaced far apart. The branches are laterally compressed at their distal ends, therefore being vertically elongated. New fi nding of Salpingoporella cemi (RADOIČIĆ) gave the new data on the variability of the shape of its branches, and on the precise stratigraphic position of the investigated localities. Besides, Salpingoporella patruliusi BUCUR is illustrated, this being its first find outside Monti Apuseni (south Carpathians) and its geographic range thus encompassing also the Dinarides. Also, a large observed number of specimens of Salpingoporella muehlbergii (LORENZ) with ramifi ed thallus makes that feature both its species-specific and generic characteristic. Quite strongly varying values of various biometric parameters, depending on the position on the thallus in one and the same specimen, raises serious questions as to their reliability and usefulness as a distinguishing factor in comparing both the specimens of one and the same species and of species of the same genus